Peningkatan Pengetahuan Kesehatan Gigi Melalui Edukasi Interaktif di Sekolah Dasar Sukabumi Selatan 01, Kebon Jeruk, Jakarta Barat - Yuliarsi, Yayuk; Komariah; Priandini, Dewi; Yuliasari, Hani; Celine; Fatwanissa; Nabila; Elline Istanto, Ie (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
The high prevalence of dental caries among elementary school children in Indonesia, reaching 93%, highlights the urgent need for effective dental health education for both students and parents. This community service activity aimed to increase knowledge and awareness about dental health through interactive education at SD Negeri Sukabumi Selatan 01, Kebon Jeruk, West Jakarta, on April 23, 2025. The target participants were 30 fourth-grade students and 15 parents, selected purposively. The program involved pre-tests, delivery of material using audio-visual media, demonstrations of proper tooth brushing techniques, group discussions, educational games, and post-tests to measure knowledge improvement. The results showed an increase in students’ average knowledge scores from 6.13 to 8.00 and parents’ scores from 7.80 to 8.60 after the intervention. The interactive method proved more effective than conventional lectures, supported by active student participation, parental involvement as role models, and strong support from the school. In conclusion, interactive education based on school-family collaboration significantly improved understanding and fostered healthy behaviors in children. It is recommended that similar activities be conducted regularly with broader parental involvement and strengthened school roles, in order to sustainably reduce dental health problems among children.